An assessment of the eResearch Knowledge Centre's support practices in the Human Sciences Research Council in Pretoria, South Africa - Baudin, Johanna Maria (Library and Information Studies Centre (LISC), 2023)
The purpose of this study was to determine whether the eResearch Knowledge Centre's (eRKC) research support services are in line with the needs of Human Sciences Research Council (HSRC) researchers. It was also intended to identify gaps in services that could be filled by additional services. The pragmatic research paradigm was used to guide the conduct of this study. This paradigm refers to a worldview that prioritizes what works in practice over what is absolutely and objectively true or real. The Research Lifecycle Model was chosen as a theoretical framework for this study because of its foundation in this paradigm. To collect data, a multi-methods cross-sectional descriptive design was used, employing both quantitative and qualitative methods. The two methods were used concurrently. A questionnaire was distributed to 156 members of the HSRC research staff in order to collect quantitative data. Interviews were conducted with nine eRKC staff members who were part of the sample to collect qualitative data. A Likert scale was used to determine whether a participant agreed or disagreed with the statements. The quantitative data analysis was done using SPSS, while the interview data were analysed using Excel. Both the quantitative and qualitative data were aligned with the six phases of the research life cycle. The findings demonstrated the effective targeting of current eRKC research support services to specific phases of the research life cycle model. The needs of HSRC researchers could be determined in each phase using this model. According to the study findings, the current eRKC research support services are aligned with the needs of HSRC researchers and highlighted services that could be expanded or promoted more effectively to HSRC researchers. It proposes a new service, data analysis, and suggests that the eRKC could play a more prominent role in research impact, research data management, and fostering collaboration with HSRC research divisions.